Prayer burns: A retrospective study - Vijay Yashpal Bhatia; Sruja Dipak Narola; Ranjit Raghu Zapadiya; Rahul Kaushik; Archana L Thakur (Wolters Kluwer Medknow Publications, 2022)
Introduction: In Indian culture, it is considered auspicious to conduct prayers before beginning one's day or even before starting to celebrate any of the festivals. The variations in conducting the prayers are numerous, but one thing which is constant is fire, which in the form of diya or candle or incense stick is always present. This many a times becomes the source of clothes catching fire leading to burns. The flame burns can cause serious complications depending on the age and the percentage of the body involved. Herein, we are presenting an article regarding the same. Methods: All burns which occurred while praying from September 2019 to September 2021 were included in the case series. Results: In our study, the patients above 60 all had comorbid conditions, and 5 out of 8 (five out of eight) patients expired that is 62.5% of the study group. These patients had the accident at home while praying where the flame from diya which is lit on the temple floor near the idol of god caught fire to the clothes. Indian females prefer to wear clothes with flairs such as chaniya choli, long Indian skirt, or saree which increases the chances of contact with diyas or source of flame leading to accidental burns. Considering that 5 (five) patients were more than 50 years of age, they survived for mean days of 16.2 days and then expired, the three younger patients recovered with an average stay of 47.3 days. Even with extensive burns due to younger age the patients recovered and did require skin grafting in the course of their treatment. Discussion: Diminished alertness of the senses, impaired mentation, slower reaction time, reduced mobility, and decreased ability of elderly people to identify the severity or risk of a situation as well as their capacity to escape from harm, puts them at higher risk of sustaining burn injury. These circumstances will also lead to larger increased total body surface area (TBSA) and deeper burns; moreover, there is an increased risk for the development of inhalation injury. These factors are closely related to a higher mortality rate. Conclusion: Age plays an important role in treatment response in a major trauma like burns. Increased age with associated co morbidities add to the severity of the burns. Younger age group however have better survival chances, though even they required prolonged hospital stay in our study considering the higher percentage of burns involved.